Speciation and complexation of dissolved Cu, Cd and Zn in Manila Bay, Philippines - Velasquez, Imelda B. (2001)
This study was done to obtain baseline data on the levels of three environmentally important dissolved metals (Cu, Cd and Zn) in Manila Bay. The different species of these metals using an operationally-defined speciation scheme (labile, bound and total) were determined and quantified, as well as the natural capacity of seawater to bind with these metals. The horizontal distribution of metals in Manila Bay showed large variations among sampling stations. Elevated levels were observed in various parts of the bay. The highest concentrations were found near point sources of Cu, Cd and Zn. this suggests that a significant source of metal pollutants in the bay could be anthropogenic in origin. Specifically, Zn and Cd concentrations at the surface were higher near the mouth of the major rivers and the surrounding provinces compared tot he stations in the middle of the bay. Cooper concentrations, however, were consistently higher and more uniformly distributed compared to Zn and Cd. The vertical distribution of the different species of dissoleved Cu, Cd and Zn collected from 18 stations and over a 24-hour period showed large vertical variation especially at the upper 20m of the water column. These differences may have become more pronounced due to the bloom of the phytoplankton, Noctilluca scintillans, at the time of the collection. The results have highlighted siginificant issues on the natural variation of substances at spatial and temporal scales. Physical (e.g., tidal oscillations) and biological processes in the bay can significantly alter the distribution, transport and speciation of metals and other substances in the water column, The presence of a very stable water column layer between the surface to 10m can limit the transport of materials from the surface to the deeper water. The occurence of a phytoplakton bloom can markedly affect the composition and type of dissolved and particulate substances and, consequently, alter the quality of the water. In addition, the presence of several rivers and industries directly draining into the bay are factors that can also cause a large variation in the behaviour, transport and distribution of dissolved Cu, Cd and Zn in the bay. Biological processes may control the distribution and complexation of Cu, cd and Zn. The natural ligands that are present in the water are generally produced form the decomposition of dead organisms and released as exudates from living organisms. The results of the complexation experiments, which showed that the [MeTotal] exceeded the [LTotal], corroborated the findings on the spatial distribution of the different metal fractions. The bay is dominated by labile species of Cu and Cd. However, the bound or unavailable Zn species were high possibly due to its coprecipitation with iron oxide which may be present during an algal bloom (e.g., Noctiluca scintillans). the continuous loading of pollutants in the bay may have caused the marked increase in the amount of dissolved metals, thereby exceeding the concentration of the natural ligands that are available in the bay. This condition, therefore, favours the increase and availability of labile and possibly more toxic metals in the bay. based on the result of this study, it may be worthwhile to consider in the adoption of the environmental criteria for metals for the calssification of water bodies, the importance of determining the concentration of metal-binding ligands. This will provide information on the natural buffering capacity of the system to reduce metal pollutants. In addition, even if the total metal concentrations do not exceed the criteria level, the amount of bioavailable metal will increase when the metal concentration approaches the ligand concentration. The uncontrolled dumping of metals in such area can result in deleterious effects to the organisms and to the ecology of the system.
Research project funded by the University throught the Office of the Vice-Chancellor from Research and Development (OVCRD).
"October 2001."
Thesis (M.S. Marine Science)--University of the Philippines Diliman.
Keywords: Water quality biological assessment -- Philippines -- Manila Bay; Water -- Pollution -- Philippines -- Manila Bay; Heavy metals -- Speciation